2013
DOI: 10.1371/journal.pone.0063059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nitrification Efficiency and Microbial Community in a Membrane Bioreactor Fed with Low COD/N-Ratio Wastewater

Abstract: In this study, an approach using influent COD/N ratio reduction was employed to improve process performance and nitrification efficiency in a membrane bioreactor (MBR). Besides sludge reduction, membrane fouling alleviation was observed during 330 d operation, which was attributed to the decreased production of soluble microbial products (SMP) and efficient carbon metabolism in the autotrophic nitrifying community. 454 high-throughput 16S rRNA gene pyrosequencing revealed that the diversity of microbial sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Several studies indicated that soil bacterial community shifts after rainforest conversion were caused by fertiliser application, liming and reduction of plant diversity (Abdi et al, 2016;Val-Moraes et al, 2016;Liu et al, 2017). We also detected the nitrification-related phylum Nitrospirae with genus Nitrospirales in oil palm aged 3.5 years, where this genus is exclusively found in the oil palm plantations (Lücker et al, 2010;Ma et al, 2013). This genus signifies higher degrees of nitrification in oil palm soils compared to rainforest, probably caused by fertiliser application and correspondingly nitrogen input, leading to more favourable conditions for nitrifiers (Ma et al, 2013;Quan et al, 2016).…”
Section: Relationships Between Bacterial Community Structure With Difsupporting
confidence: 58%
See 1 more Smart Citation
“…Several studies indicated that soil bacterial community shifts after rainforest conversion were caused by fertiliser application, liming and reduction of plant diversity (Abdi et al, 2016;Val-Moraes et al, 2016;Liu et al, 2017). We also detected the nitrification-related phylum Nitrospirae with genus Nitrospirales in oil palm aged 3.5 years, where this genus is exclusively found in the oil palm plantations (Lücker et al, 2010;Ma et al, 2013). This genus signifies higher degrees of nitrification in oil palm soils compared to rainforest, probably caused by fertiliser application and correspondingly nitrogen input, leading to more favourable conditions for nitrifiers (Ma et al, 2013;Quan et al, 2016).…”
Section: Relationships Between Bacterial Community Structure With Difsupporting
confidence: 58%
“…We also detected the nitrification-related phylum Nitrospirae with genus Nitrospirales in oil palm aged 3.5 years, where this genus is exclusively found in the oil palm plantations (Lücker et al, 2010;Ma et al, 2013). This genus signifies higher degrees of nitrification in oil palm soils compared to rainforest, probably caused by fertiliser application and correspondingly nitrogen input, leading to more favourable conditions for nitrifiers (Ma et al, 2013;Quan et al, 2016). The fertiliser regime increased certain bacteria population such as Firmicutes which was prevalent in the oil palm area with 1.5-year old palms where the application of fertiliser increased the pH and phosphate level in the soil ( Table 5).…”
Section: Relationships Between Bacterial Community Structure With Difmentioning
confidence: 70%
“…Also, nitrite accumulation was reported at low C:N values in studies using a 35-L SBR (~2 mg COD/mg TN) [39], a lab-scale 6.3-L SBR (3.33 mg COD/mg NH4 + -N) [41], and a pilot-scale continuous-flow A/O/A reactor (3.19 mg COD/mg NH4 + -N) [40]. On the other hand, there was complete nitrification without nitrite accumulation at low influent C:N (3 ± 1 mg COD/mg TN) in pilot-scale membrane batch reactors [38], similar to our results. Increasing C:N molar ratios from 2 to 5 was shown to significantly reduce nitrification rates in a laboratory denitrification-nitrification system [71], although the study did not mention whether this caused nitrite accumulation.…”
Section: Importance Of Assessing F:m C:n and Srt Simultaneously For mentioning
confidence: 99%
“…Influent manipulation in particular has been reported to yield contrasting results in terms of C:N [37]. Low influent C:N values (2-3 mg COD/mg TN) have been shown to prevent [38], but also promote [39][40][41] nitrite accumulation in different sludge systems. Other studies have reported nitrite accumulation at high (10 mg COD/mg NH4 + -N) [42] and also fluctuating influent C:N values (2.5-8 mg COD/mg NH4 + -N) [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Under different operational conditions such as HRT, SRT, DO concentration, temperature, and substrate concentration the responses of autotrophic nitrifiers are divergent, which in turn influence metabolite production (Hu et al 2003). In low C/N ratios, nitrifiers dominate heterotrophs and enhance the nitrification efficiency (Ma et al 2013). Ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB), contributors of two phylogenetically unassociated congregations of lithoautotrophic bacteria, perform nitrification process via a symbiosis interaction.…”
Section: Introductionmentioning
confidence: 99%